READINESS DALAM BELAJAR - Arifan Ananda; Qonita Masyithah, Hidayani Syam (ADISAM PUBLISHER, 2025)
Readiness in learning is an essential condition that influences an individual's ability to respond and achieve learning objectives. Learning readiness involves several factors: attention, motivation, developmental maturity, discipline, and self-confidence. Attention is the ability to focus on learning tasks, motivation is the internal drive that propels individuals to learn, and developmental maturity encompasses cognitive, emotional, social, and physical readiness. Discipline helps shape readiness through the influence of a supportive and authoritative environment, and by modifying body movements to enhance self-confidence. The principles of readiness formation include the interaction of developmental aspects, physical and mental maturity, the positive influence of experiences, and specific periods during development. High motivation, interest in the subject matter, psychological and emotional readiness, physical readiness, and environmental support are key factors in forming learning readiness. Environment and culture also play significant roles in learning readiness. Social support, a positive learning culture, adequate facilities and resources, and an inclusive environment that supports achievement can enhance an individual's motivation and readiness to learn. By understanding and facilitating these factors, effective and meaningful learning can be achieved, allowing students to maximize their potential